THE PROVISIONS OF WATER AND GARBAGE POLLUTION IN STREET, DRAINAGE AND BUILDING ACT, 1974: A VIEW IN ISLAMIC LAW (UUM Journal of Legal Studies, 2020)
The statute relating to environmental conservation plays an important role to protect water and garbage pollution. The establishment and enforcement of the Street, Drainage and Building Act 1974 is to protect the people’s rights and interests in order to safeguard the environment from being polluted. There are a few provisions in this Act relating to water and garbage pollution and protection of water resources from any pollution. Therefore, this article will examine the provisions in relation to water and garbage pollution in the Act and then identify similar discussions in Islamic law, which deal with the protection of water and garbage pollution. A qualitative method is used to obtain data for this paper. Analysis of documents from primary and secondary sources was executed inductively, deductively and comparatively using the Act and Islamic reference sources which was then documented in a descriptive report.